Monday

December 22, 2014

December 22, 2014

Posted by **Craig** on Wednesday, January 28, 2009 at 1:43pm.

2) show that: 1-(cos2t divided by (cos x cos)t)= (TAN x TAN)t

- trigonometry -
**drwls**, Wednesday, January 28, 2009 at 2:06pmIs cos2t supposed to represent cos^2 t or cos (2t)?

In either case, the expression is not a correct identity. I believe you copied the problem incorrectly. It should be

1-cos^2t divided by sin^2t = 1

In your second question, (tan x tan) t is not an accepted notation. Do you mean tan^2 t?

[1 - cos^2 t]/cos^2 t = sin^2 t/ cos^2 t

= tan^2 t

**Answer this Question**

**Related Questions**

Trig. - sec^2xcotx-cotx=tanx (1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times...

Trigonometry desperate help, clueless girl here - 2. solve cos 2x-3sin x cos 2x...

trigonometry - show that 1-cos^2t divided by sin^2t =TANt

precalculus - For each of the following determine whether or not it is an ...

Trig - Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < ...

Trigonometry - 1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two ...

Trigonometry - Please review and tell me if i did something wrong. Find the ...

Math-Trigonometry - Show that if x, y, and z are consecutive terms of an ...

trig - Show that 1-cos2A/Cos^2*A = tan^2*A 1-cos2A/Cos^2*A = [Cos^2(A) - Cos(2A...

TRIG - what is another form of: sin (A+B) sin (A-B)/ cos^2 A cos^2 B a) cos^2 A...